Job satisfaction among community drug distributors in the Mass Drug Administration programme in Nigeria: a cross-sectional study. (24th March 2023) - Kevin, Diltokka Gideon; Lawong, Bernsah Damian; Dixon, Ruth; Woode, Maame Esi; Agboraw, Efundem; Ozano, Kim; Dean, Laura; Forrer, Armelle; Isiyaku, Sunday; Thomson, Rachael; Worrall, Eve
Abstract: Background: Despite having one of the largest human resources for health in Africa, the delivery of neglected tropical disease (NTD) health interventions in Nigeria has been hampered by health worker shortages. This study assessed factors associated with job satisfaction among community drug distributors (CDDs) supporting the Nigerian NTD programme, with the goal of identifying opportunities to improve job satisfaction in support of NTD control and elimination efforts in Nigeria. Methods: A health facility-based cross-sectional survey was conducted in 2019 among CDDs in two states with sharply contrasting NTD programme support, Kaduna and Ogun. A multivariate logistic regression model was used to determine the association between respondent characteristics, programme delivery modalities and job satisfaction. Results: Overall, 75.3% and 74.0% of CDDs were categorised as being satisfied with their job in Kaduna and Ogun states, respectively. The component with the highest reported satisfaction was motivation, where 98.9% and 98.6% of CDDs were satisfied, in Kaduna and Ogun, respectively. Participants were least satisfied with remuneration, communication, supplies and materials, as well as workload. Location (rural/urban) and state, years of experience, who delivers training and reimbursement of transport fare during medicine distribution were significantly associated with job satisfaction. Conclusions: Including multiple health staff and NTD programme cadres in CDD training and providing remuneration to cover transport fares spent during MDA delivery may improve CDDs' job satisfaction both in Ogun and Kaduna states. Given these two states are at opposite ends of the programme support spectrum, such adaptative measures might help improve CDD job satisfaction in the wider Nigerian NTD programme context.